Obstructive jaundice at the initial presentation in small-cell lung cancer - Ochi, Nobuaki (Dove Medical Press, 2010)
Obstructive jaundice sometimes may develop in association with advanced small-cell lung cancer (SCLC); however, SCLC initially presenting with obstructive jaundice is rare. This report presents the cases of two SCLC patients with obstructive jaundice at the initial diagnosis. A 64-year-old male presented with obstructive jaundice due to a tumor at the head of the pancreas. He was diagnosed with SCLC by transbronchial biopsy from a lung tumor in the left upper lobe. Another 74-year-old male was admitted with jaundice due to a tumor in the porta hepatis. He was also diagnosed with SCLC by a fine-needle aspiration biopsy of a lung tumor in the left lower lobe. Both cases were successfully treated with systemic chemotherapy after endoscopic retrograde biliary drainage.